Idiopathic pulmonary fibrosis: the need for early diagnosis - Cicchitto, Gaetano; Sanguinetti, Claudio M. (Multidisciplinary Respiratory Medicine, 2013)
Idiopathic pulmonary fibrosis (IPF), a chronic fibrosing lung disease of a progressive nature and unknown etiology, has the largest epidemiological impact and the worst prognosis among the idiopathic interstitial pneumonias (IIP). Despite the progress in pathogenetic knowledge, many aspects are still dubious, in particular the biomolecular mechanisms activated in the early stages of the disease. Early diagnosis is desirable not only to better define aspects of the natural history of the disease, but also to customize treatment protocols. An early diagnosis of IPF should necessarily be based on the ability to highlight a number of features drawn not only from a careful composition of specific anamnestic data with clinical, functional and radiological parameters, but also from biological markers that, in a proper context, can provide guidance and confirm a clinical-anamnestic suspicion. The identification of specific biomarkers for IPF is a modern and attractive look for the potential clinical implications in terms of diagnosis, prediction of disease progression and prognosis. Biomolecular investigations on IPF were performed selectively on tissue samples, bronchoalveolar lavage (BAL), or blood: nowadays the “multi-omic” approach may allow studying individual constitutional profiles resorting to a series of biomolecular disciplines, the so-called “omics”, which focuses on responses of the entire genomic complex, in line with the current trend to quantitatively analyze the interactions of all components of a biological system. Such refined investigations are an essential base for research now, but they might become a routine in the near future, allowing a more precise classification of patients suffering from a disease of unclear taxonomy.